Reactor performance, biofilm property and microbial community of anaerobic ammonia-oxidizing bacteria under long-term exposure to elevated Cu (II) - Ma, Yongpeng; Yuan, Dongli; Mu, Bailong; Zhou, Jianuan; Zhang, Xiaojing (International biodeterioration & biodegradation, 2018)
In this study, the variation of reactor performance, biofilm property and microbial community in response to the elevated Cu (II) in Anammox system were investigated. The nitrogen removal, extracellular polymeric substance (EPS) and copper content in biofilm, soluble microbial products (SMP), dehydrogenase activity (DHA) and microbial community were evaluated. The self-recovery ability was also investigated after stopping Cu (II) supply. Results showed the long-term feeding of Cu (II) significantly suppressed the nitrogen removal in Anammox system. The nitrogen removal rate (NRR) decreased to 0.210, 0.145 and 0 kg m−3 d−1, respectively in 1, 5 and 10 mg L−1 Cu (II), from the initial 0.50 kg m−3 d−1, with the decreasing ratio of 57.3%, 71.0% and 100%. With the elevation of Cu (II), the SMP, EPS and copper content gradually increased while DHA sharply decreased. Cu (II) improved the microbial diversity and lowered the Candidatus Kuenenia abundance to 1.36% from the initial 6.50%. The self-recovery ability of Anammox system was unsatisfactory, the NRR only recovered to 26.7% after one month operation free from Cu (II). Finally, the mechanism of Cu (II) interacting with Anammox biofilm was analyzed. •The mechanism of Cu (II) interacting with Anammox biofilm was proposed.•10 mg L−1 Cu (II) decreased the nitrogen removal to 0 in Anammox system.•Copper content in biofilm was the key factor affecting AAOB bioactivity.•Copper content showed negative correlation with both NRR and DHA.•Cu (II) performed more durable inhibition on AAOB bioactivity than on the microbial community.